Mixed convection flow of Brinkman fluid with convective boundary condition at lower stagnation point of horizontal circular cylinder - Siti Farah Haryatie, Mohd Kanafiah; Abdul Rahman, Mohd Kasim; Syazwani, Zokri; Al-Sharifi, H. A. M. (Penerbit UMP, 2021)
Convective heat transfer occurs when heat is transferred from one level to another upon the motion of fluid. Understanding on the characteristics of fluid flow is essential since it will produce the desired output of the product. therefore, this paper examines the mixed convection flow at lower stagnation point of horizontal circular cylinder on Brinkman fluid saturated in porous region with convective boundary condition. The influence of Brinkman, mixed convection and conjugate parameter on the flow field are studied. To reduce the complexity of the equations, a suitable similarity transformation is used. The numerical results of governing equations are obtained via bvp4c tools in Matlab. The effect of mixed convection, Brinkman and conjugate parameter on the temperature and velocity profile, skin friction coefficient together with Nusselt number are analysed and portrayed in graph and table form. The velocity profile increased with improving mixed convection and conjugate value, but decreased with increasing Brinkman factor. It is also discovered that the temperature decrease when the mixed convection parameter increase. This theoretical results will benefit the researchers, particularly in the manufacturing industry, in validating experimental study data.